Organizational Justice and Employee Readiness for Change: The Mediating Role of Perceived Organizational Support - Kebede, Senay; Wang, Aimin (Frontiers in Psychology, 2022)
Recent studies have shown that an organization must adapt to change to succeed in a constantly changing market. However, most change efforts fail due to employee resistance to change. It is critical to address employee readiness for change to avoid employee resistance. Employees’ perceptions of fair treatment by their organizations have positively predicted their readiness for organizational change. This research aims to investigate the influence of organizational justice on employee readiness for change using perceived organizational support as a mediator. This study was carried out on the Ethiopian Revenue and Customs Authority and conducted with 359 employees. The study used a structural equation model and multiple regression analysis. The model developed explains how perceived organizational support mediates the positive relationship between organizational justice and employee readiness for change. The result shows that organizational justice is a significant influencing factor on employee readiness for change. Furthermore, perceived organizational support mediates the positive influence of organizational justice on employee readiness for change. This study contributes to the literature on organizational justice, organizational change, and change readiness. This study can also assist public and private organizations, as well as policymakers and practitioners, in improving organizational change practices. Overall, this study concludes that all organizations in Ethiopia, including Ethiopian Revenue and Customs Authority, must investigate the influence of organizational justice on employee readiness for change to have successful organizational change.